Erratum: JESSICA D. PETERSEN, MATTHEW J. PETERSEN & GREGORY W. COURTNEY (2012). Description of a new subgenus Neophylidorea (Diptera: Tipulidae) and a new species. Zootaxa, 3555, 40–54. - Petersen, Jessica D.; Petersen, Matthew J.; Courtney, Gregory W. (Zootaxa, 2012)
(Erratum)